Worlding Miss World, Bangalore, 1996. Issue 3 (3rd May 2016) - Mazzarella, William
Abstract : This essay revisits the much-discussed swarm of protests surrounding the 1996 Miss World pageant in Bangalore, India. It suggests that behind the clamour of clashing opinions regarding the content of the pageant lay a deeper crisis, uninterrogated yet constantly palpable: the absence of a performative dispensation within which the then-nascent project of liberalisation could, paradoxically, be experienced as self-grounding. By organising its discussion around interviews with some of the people most directly involved in trying to manage the meaning of the event – through sponsorship, public relations, policing, and protest – the essay shows how a reconsideration of the pageant can help us understand the delicate relation between commercial publicity and sovereign authority in a globalising age.